Regulation of amino-acid metabolism controls flux to lipid accumulation in Yarrowia lipolytica - Kerkhoven, Eduard J; Pomraning, Kyle R; Baker, Scott E; Nielsen, Jens (NPJ systems biology and applications, 2016)
Yarrowia lipolytica is a promising microbial cell factory for the production of lipids to be used as fuels and chemicals, but there are few studies on regulation of its metabolism. Here we performed the first integrated data analysis of Y. lipolytica grown in carbon and nitrogen limited chemostat cultures. We first reconstructed a genome-scale metabolic model and used this for integrative analysis of multilevel omics data. Metabolite profiling and lipidomics was used to quantify the cellular physiology, while regulatory changes were measured using RNAseq. Analysis of the data showed that lipid accumulation in Y. lipolytica does not involve transcriptional regulation of lipid metabolism but is associated with regulation of amino-acid biosynthesis, resulting in redirection of carbon flux during nitrogen limitation from amino acids to lipids. Lipid accumulation in Y. lipolytica at nitrogen limitation is similar to the overflow metabolism observed in many other microorganisms, e.g. ethanol production by Sacchromyces cerevisiae at nitrogen limitation. Biofuels: Yeast produces fatty oils in absence of nitrogen When nitrogen is in short supply, the yeast Yarrowia lipolytica redirects its energy production from protein building blocks to fatty lipids. Scientists hope to use Y. lipolytica as a microbial factory to produce fat-based biofuels, and these findings could help them create cells with greater lipid yields. A team led by Eduard Kerkhoven from Chalmers University of Technology in Göteborg, Sweden, constructed a comprehensive metabolic model of Y. lipolytica grown in a bioreactor under different nutrient conditions. At low nitrogen levels, the researchers observed lipid accumulation in the cell, although the regulation of fat metabolism was unchanged. What did change was amino acid synthesis, which was tamped down, leading to an overflow in fat production–in the same way that baker’s yeast, Saccharomyces cerevisiae , produces ethanol when nitrogen is limited.